2016
DOI: 10.1186/s12936-016-1590-1
|View full text |Cite
|
Sign up to set email alerts
|

Risk assessment of malaria in land border regions of China in the context of malaria elimination

Abstract: BackgroundCross-border malaria transmission poses a challenge for countries to achieve and maintain malaria elimination. Because of a dramatic increase of cross-border population movement between China and 14 neighbouring countries, the malaria epidemic risk in China’s land border regions needs to be understood.MethodsIn this study, individual case-based epidemiological data on malaria in the 136 counties of China with international land borders, from 2011 to 2014, were extracted from the National Infectious D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 22 publications
2
25
0
Order By: Relevance
“…Many infectious diseases, such as P. vivax malaria, dengue fever, influenza A(H1N1), epidemic hemorrhagic fever, JE, chikungunya, Lyme disease, scrub typhus, and VL, are found frequently in the indigenous population of China, but some are found more often as imported diseases, such as P. falciparum malaria, yellow fever, Zika virus, and MERS. Imported P. falciparum malaria is a major obstacle to achieving malaria elimination in China (12)(13)(14). This study showed that malaria was the most frequent imported infectious disease during 2005-2016, and Yunnan was the province with the greatest number of cases of imported malaria, which was consistent with other relevant studies in China (15)(16)(17).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Many infectious diseases, such as P. vivax malaria, dengue fever, influenza A(H1N1), epidemic hemorrhagic fever, JE, chikungunya, Lyme disease, scrub typhus, and VL, are found frequently in the indigenous population of China, but some are found more often as imported diseases, such as P. falciparum malaria, yellow fever, Zika virus, and MERS. Imported P. falciparum malaria is a major obstacle to achieving malaria elimination in China (12)(13)(14). This study showed that malaria was the most frequent imported infectious disease during 2005-2016, and Yunnan was the province with the greatest number of cases of imported malaria, which was consistent with other relevant studies in China (15)(16)(17).…”
Section: Discussionsupporting
confidence: 90%
“…The reason for the large number of imported cases is that Yunnan Province has long international borders with Myanmar, Laos, Vietnam, and other countries of the Greater Mekong Subregion that show a high incidence of malaria (16). The persons who cross these borders to enter or leave China increase opportunities for infectious diseases to be imported from adjacent countries (3,14,18,19), especially from Myanmar (12,13,20). P. falciparum malaria was imported mainly from Ghana and P. vivax malaria mainly from Asia, which was consistent with Zhou's findings (5).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The proportion of malaria deaths attributed to P. falciparum was 87.7% and 6.8% by P. vivax. These results were consistent with other reports [19,[21][22][23].…”
Section: Epidemiology and Infectionsupporting
confidence: 94%
“…Moreover, the malaria vector mosquitos still thrive with the potential to transmit any imported cases that may be missed. This situation is additionally challenged by the complicated ecological settings along the Yunnan border areas, neighboring three malaria endemic countries: Lao People's Democratic Republic, Myanmar, and Vietnam [1][2][3], as well as the importation of cases from Chinese workers returning from outside the region, such as from Africa. Estimates of these imported cases exceed over 2500 per year and have impacted almost all provinces of China over the past decade.…”
Section: Prevention Of Malaria Retransmission By Monitoring the Impormentioning
confidence: 99%